PEDAGOGICAL APPROACHES TO DRAWING HUMAN FIGURES THROUGH GROUP WORK AND COLLABORATION - Rahmatova Aziza Ahmatovna (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This article examines pedagogical approaches to teaching students to draw human figures through group work and collaborative activities. The study highlights the benefits of peer learning, teamwork, and interactive methods in developing technical skills, observational abilities, and creative expression. Strategies for structuring collaborative exercises, providing constructive feedback, and fostering a supportive learning environment are discussed. Emphasis is placed on how cooperative learning can enhance students’ confidence, motivation, and artistic competence while encouraging experimentation and personal expression.